Budget harmonization and challenges: understanding the competence of professionals in the budget process for structural and policy reforms in public libraries. Issue 2 (6th May 2020) - Rafi, Muhammad; Ahmad, Khurshid; Bin Naeem, Salman; Jianming, Zheng
Abstract : Purpose: In the past, the field of public libraries proved to be a neglected area of government in terms of allocating handsome budgets for adequate services and developing infrastructure. The aim of this research is (1) to understand the level of library professionals and associated challenges in the preparation and implementation of the budget in public libraries and (2) to analyze the annual grand and regular library budget allocated to public libraries. Design/methodology/approach: A comprehensive literature search was carried out from work published in the past – the quantitative study based on a structured research questionnaire followed by the five-point Likert scale. The primary data were collected by distributing printed questionnaires among the library professionals serving in the directorate of public libraries and its suboffices. The secondary data "Budget Grand" for seven years (2009–2015) and the regular budget for two years (2015–2016) were collected from seven public libraries, and data on the district population and literacy rate were obtained from the provincial bureau of statistics. The authors used the one-way ANOVA on primary data to determine the average difference between samples and descriptive statistics on secondary data. Findings: Survey results show that budgeting is a useful tool for predicting the future, controlling resources and improving employee performance and departmental levels. The findings disclosed that the annual budget review includes guidelines for implementation without adequate discussion and guidance for overcoming challenges. In addition to increasing print and database resources, currency fluctuations, unfair resource allocation and budgeting processes proved to be a potential obstacle to the execution of the library budget. Moreover, library material usage and regular membership are decreasing compared to literacy rates in each district of the province. It also turned out that the limited resources in a library compared to the population and the insufficient budget for operation, maintenance and other library processes posed another challenge for the administration. Practical implications: The results, which are based on the primary data of experts and the secondary data on the library budget, can help the directorate of public libraries to push ahead with budgetary reforms and overcome challenges. Social implications: This article outlines some basic steps for librarians, publishers and sellers to cope with changes caused by currency fluctuations and falling budget pressures. Given the regional population, literacy gaps and the current state of libraries, the results could also cause the government to expand the public library network across the province. Originality/value: The study builds upon the qualitative method using a questionnaire and on the secondary data for an in-depth understanding of the whole budgetary process. This comprehensive coverage of the budgeting process provides professionals with useful information in preparing a balanced budget for public libraries.